Profitability Beyond Size: How Working Capital Efficiency Creates Value Across Industries - Ika Prayanthi; Danny Ivan Rantung; Nouke Sysca Oroh (Indonesian Journal Economic Review (IJER), 2026)
This study investigates the effect of working capital efficiency on firm profitability across multiple sectors in Indonesia. Panel data covering 1,012 firms listed on the Indonesia Stock Exchange over the period 2014–2024 yielded 5,273 firm-year observations. Working capital efficiency was measured using three proxies: winsorized Cash Conversion Cycle, Inventory Turnover, and Accounts Receivable Turnover, while profitability was proxied by Profit Margin as the primary dependent variable. Multiple linear regression was estimated while controlling for firm size (Ln Market Cap) and industry sector using the open-source Jamovi software version 2.x. Our findings indicate that the Cash Conversion Cycle has a statistically significant negative effect on Profit Margin (b = –0.0067, p < 0.001). Inventory Turnover also exhibits a significant negative effect (b = –0.0116, p = 0.025), whereas Accounts Receivable Turnover demonstrates a positive effect (b = 0.0267, p = 0.032). Firm size emerges as the strongest predictor of profitability (b = 4.6579, p < 0.001). We observe substantial sectoral heterogeneity, with the property, transportation, and utility sectors showing significantly lower profit margins compared to the financial sector. These findings confirm the importance of efficient working capital management in enhancing financial performance, with mechanisms varying across industry sectors. This research contributes to the financial management literature by providing large-scale empirical evidence from an emerging market in Southeast Asia, while documenting cross-sectoral heterogeneity that explains inconsistent findings in prior research.